2023
DOI: 10.1002/jum.16384
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Ultrasound Evaluation of Diastasis Recti Abdominis During Different Gestational Periods

Xiao‐Han Guo,
Hua Wang,
Sheng‐Jiang Chen
et al.

Abstract: ObjectiveThe purpose of this study is to explore the application value of two‐dimensional ultrasound and shear wave elastography (SWE) in the multidimensional evaluation of diastasis recti abdominis (DRA) during different gestational periods.MethodsA cohort of 202 gravidas that were examined in our hospital between June 2021 and September 2022 were selected for the purpose of the study, which included 26 cases with <14 weeks of pregnancy, 36 cases in the 14th–27th week of pregnancy, 36 cases in the 28th–34t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Guo et al investigated the application of two-dimensional ultrasound and SWE in assessing DRA at various gestational periods ( Guo et al, 2024 ). Their study showed that the Young’s modulus of the rectus abdominis was positively correlated with the thickness of rectus abdominis (r = 0.408), consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al investigated the application of two-dimensional ultrasound and SWE in assessing DRA at various gestational periods ( Guo et al, 2024 ). Their study showed that the Young’s modulus of the rectus abdominis was positively correlated with the thickness of rectus abdominis (r = 0.408), consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%